Fractionation and physicochemical characterization of dietary fiber of kenaf (Hibiscus cannabinus L.) seed - Nevara, Gita Addelia; Syed Muhammad, Sharifah Kharidah; Zawawi, Norhasnida; Mustapha, Nor Afizah; Karim, Roselina (John Wiley and Sons, 2024)
Kenaf seeds are underutilized kenaf plant by‐products, containing essential nutrients including dietary fiber (DF), which can be potentially utilized as food ingredients. The present study aimed to evaluate the physicochemical characteristics of kenaf seed fiber fractions extracted from kenaf seed.Defatted kenaf seed powder yielded four DF fractions: alkali‐soluble hemicellulose (146.4 g kg−1), calcium‐bound pectin (10.3 g kg−1) and acid‐soluble pectin (25.4 g kg−1) made up the soluble fibre fraction, whereas cellulose (202.2 g kg−1) comprised the insoluble fraction. All fractions were evaluated for their physicochemical properties. The DF fractions contained glucose, mannose, xylose and arabinose, and a small amount of uronic acid (1.2–2.7 g kg−1). The isolated pectin fractions had a low degree of esterification (14–30%). All the isolated DF fractions had high average molecular weights ranging from 0.3 to 4.3 × 106 g mol−1. X‐ray diffractogram analysis revealed that the fractions consisted mainly of an amorphous structure with a relative crystallinity ranging from 31.6% to 44.1%. The Fourier‐transform infrared spectroscopy spectrum of kenaf seed and its DF fractions showed typical absorption of polysaccharides, with the presence of hydroxyl, carboxyl, acetyl and methyl groups. Scanning electron microscopy analysis demonstrated that the raw material with the rigid structure resulted in soluble and insoluble DF fractions with more fragile and fibrous appearances, respectively. The soluble DF demonstrated greater flowability and compressibility than the insoluble fractions.These findings provide novel information on the DF fractions of kenaf seeds, which could be used as a potential new DF for the food industry. © 2023 Society of Chemical Industry.